Geochemical records of Lake Erhai (South-Western China) reveal the anthropogenically-induced intensification of hypolimnetic anoxia in monomictic lakes. (15th April 2022) - Zhang, Yongdong; Fu, Huan; Liao, Hanliang; Chen, Huihui; Liu, Zhengwen
Abstract: In monomictic lakes, hypolimnetic anoxia is becoming severe in extent and duration over the past few decades. Understanding historical trends in hypolimnetic dissolved oxygen (DO) levels and the factors controlling them is crucial for effective protection and management of monomictic lakes everywhere, but the issue remains little studied in China. Here, our study elucidated the variation of hypolimnion DO and organic matter (OM) input in Lake Erhai (a typical monomictic lake in South-Western China) during the past 200 years, by using the geochemical profiles of elements (C, N, P, S, Mo, Ca, and Al) and aliphatic hydrocarbons in a dated sediment core. The values of element proxies (S concentrations, S/Al ratios, Mo enrichment factor, and total organic carbon/total P ratios) and pristane/phytane (Pr/Ph) ratios reflect relatively limited development of anoxia in the lake hypolimnion before 1990. Meanwhile, the n -alkane proxies (short-chain, middle-chain, and long-chain n -alkane abundances, n -C17 / n -C16 alkane ratios, and Paq) indicate relatively scant inputs of OM from phytoplankton and relatively high inputs of OM from terrestrial plants or from submerged macrophytes. Taken together the results show that OM supplied in this period did not deteriorate hypolimnion DO in Lake Erhai. The element proxies and Pr/Ph ratios point to that the lake had experienced a pronounced intensification of hypolimnetic anoxia after 1990, and the n -alkane proxies indicate that the lake was susceptible to severe eutrophication and phytoplankton blooms in this period. The synchronous sharp variation implies the decay of massive phytoplankton OM had severely consumed oxygen in the lake hypolimnion. The large surface area/depth ratio in Lake Erhai is conducive for an overturn of the water column during wind disturbance, which allowed the water column stratification and relating effects (e.g., hypolimnetic anoxia) less vulnerable to some aspects of climate change. Graphical abstract: Image 1 Highlights: We elucidated the dynamics of hypolimnion DO and OM input in Lake Erhai. Increased hypolimnetic anoxia in Lake Erhai was driven by massive input of phytoplankton OM. Dominant input from terrestrial plants correspond to weak hypolimnetic anoxia. Increased input of submerged macrophytes cannot deteriorate hypolimnion DO. The high surface area/depth ratio in Lake Erhai counteracts the climate warming effects.